The Capacitive Property Enhancement of CoFeP-Ni(OH)2/Nickel Foam Electrodes via an Interfacial Integration Strategy for Asymmetric Supercapacitors - Meiying Cui; Meiying Pei; Seok Kim (Molecules, 2025)
We report the fabrication of CoFeP-Ni(OH)2/nickel foam (NF) composite electrodes via a two-step strategy involving the hydrothermal synthesis of Ni(OH)2 on nickel foam followed by the electrochemical deposition of CoFeP. The integration of the Ni(OH)2 interlayer not only provides a structurally robust interface but also facilitates synergistic redox activity, thereby significantly boosting the pseudocapacitive behavior of the electrode. Comparative analysis with bare CoFeP/NF reveals that the presence of the Ni(OH)2 layer contributes to enhanced charge transfer efficiency and an increased electroactive surface area. Among the samples prepared under varying deposition cycles, the optimized CoFeP-Ni(OH)2/NF electrode exhibits a high areal capacitance of 4244 mF cm−2 at 2 mA cm−2. Furthermore, an asymmetric supercapacitor device assembled with CoFeP-Ni(OH)2/NF as the positive electrode and activated carbon as the negative electrode delivers a maximum energy density of 0.19 mWh cm−2 at a power density of 0.37 mW cm−2 and excellent cycling stability, retaining 72% of its initial capacitance after 5000 cycles at a high current density of 8 mA cm−2.